Recurrent Acute Pancreatitis as A Manifestation of Sphincter of Oddi Dysfunction - Ira Laurentika; Ari Fahrial Syam; Marcellus Simadibrata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2016)
Recurrent acute pancreatitis (RAP) is defined as two or more occurance of acute pancreatitis with no evidence of underlying chronic pancreatitis. Prevalence of RAP varied from 10-30%. One of the postulated mechanism of this condition is sphincter of Oddi dysfunction (SOD) which is a clinical biliary pain syndrome or acute pancreatitis (AP) due to pancreatobiliary obstruction  at the level of sphincter of Oddi.  We reported a 29-year-old female patient who came to Cipto Mangunkusomo Hospital regarding upper quadrant abdominal pain with previously well documented history of AP in the last six months before admission.  Laboratory findings showed elevated pancreatic enzyme level which was consistent with AP.  The patient underwent magnetic resonance cholangio-pancreatography (MRCP) and endoscopic ultrasound (EUS) examination and both of the results showed dilatation of pancreatic duct which suggested SOD.  Due to the lack of further diagnostic modality, manometry was not performed on this patient. However, after excluding other possible etiology of SOD, the patient underwent endoscopic retrograde cholangio-pamcreatograhy (ERCP) and sphincterotomy was performed.  The signs and symptoms of AP was relieved after sphincterotomy and not yet recurred.